PTH-166 Patient Preference for the Management of Chronic Gastrointestinal Disorders. (4th June 2013) - Donnelly, R E; Reynolds, N; Todd, J A; Henry, E B; Mowat, C; Groome, M
Abstract : Introduction: Gastroenterology has a large and expanding outpatient workload, much of which deals with chronic relapsing disorders. In our Scottish Teaching Hospital it is the second busiest speciality by referral rate leading to intense pressure on resources such as clinic. Traditionally many patients with chronic disease had regular clinic regular follow-up which may not always be clinically required. The objective of this study was to establish whether there were alternative review methods to traditional clinic appointments that could be employed to reduce pressure on overstretched clinics. Methods: A questionnaire was devised and given to patients in various gastroenterology outpatient clinics who fulfilled the inclusion criteria. Clinics included the IBD, liver and general GI clinics. The questionnaire asked patients to rank their preferred method of follow-up. Options included: Pre-scheduled Doctors Appointment, Open Doctors Appointment, Teleconsultation, Email Consultation, Letter Consultation, Specialist Nurse Appointment, Self Management Plan and No follow Up. Data was analysed for preference trends among different epidemiological groups including age, sex, disease type and postcode deprivation. Results: Questionnaires were completed by 106 patients (62 females: 43 males). The age of patients ranged between 18 and 86, with average age of 46.6 and median age of 50. Analysis was carried out looking for trends of preference among different groups (18–39, 40–64, 65–90). No deprivation bias was identified in this study. There were no significant patterns of preference observed between sexes or disease type. In all age groups the top three choices were a regular clinic appointment with a doctor, an open appointment or a teleconsultation. Conclusion: Gastroenterology outpatient clinics are in grave need of a system to reduce workload. Chronic, relapsing conditions could be subject to other methods of follow-up given their nature. Whilst new follow-up methods could be the solution current patient preference is for traditional doctor led clinic appointments. Any change from this will require patient education and support. Surprisingly modern methods such as virtual clinics by email were not popular and had no significant preference with the younger age groups. From this data we plan to explore telephone consultations as a means to reduce pressure on out patient clinics. Disclosure of Interest: None Declared.